IDENTIFIKASI DAN POTENSI PARASIT PADA SUMBER DAYA IKAN HIAS DI DANAU LAIS KALIMANTAN TENGAH - Rosita Rosita; Arthut Mangalik; M. Adriani; M. Mahbub (EnviroScienteae, 2012)
This study aims to identify and inventory of  potentially pathogenic species of parasites cause disease in ornamental fish, both caught in the Lais lake and the domestication activities. Beside is to know  The relationship between water quality with a prevalence, intensity and dominance of parasites that attack ornamental fish in domestication.  The reseach activities were conducted since  January 20, 2010 until March 16, 2010.  The fish samples collected from the fishermen  were identificated   and  inventoried by means of recording of parasite type, amount and organs  attack the fish using the identification book (Kabata, 1985) and the identification key of parasite by Bykhovskaya, et al. (1964) and calculated the value of prevalence, intensity and domination. The results showed four parasitic protozoan species were  Myxobolus sp, Glossatella sp, Vorticella sp., Chilodonella sp. and one species of non-protozoan  (worms) was  Dactylogyrus sp. in Lais lakes and in the  domestication. The parameter of water quality  such as  temperature, DO, pH and NH3  have  relationship to total of  parasites, parasite prevalence and intensity of attacks.   The value range of water quality parameters of  Lais lake where  temperature 27.68 0C-28 730C, DO 3.00-5.98 mg/L, pH 5.19-5.84 and NH3 0.01-0.02 mg/L.  The value range of  water quality of domestication activities were   temperature 27.83 0C-28.51 0C, DO 5.38-6.38 mg/L, pH range on average from 5.60-6.41 and ammonia (NH3) average ranged from 0.02-0.01 mg/L.  The above range values  showed  the optimum range of water quality for fish and they support for the health of fish.